On the asymptotic expansions in the local theorems - Karoblis, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Кароблис. Об асимптотических разложениях в локальных теоремах A. Karoblis. Apie asimptotinius skleidinius lokalinėse teoremose